How environmental effort drives performance through competitive advantage in the Indonesian recycling industry - Agustiani, Sekar Ayu; Sabihaini, Sabihaini; Effendi, Mohamad Irhas (Asian Management and Business Review, 2025)
This study explores the influence of corporate efforts in managing natural resources (ESD) on sustainable performance, specifically its economic and social dimensions, in Indonesia’s recycling industry, emphasizing the mediating role of competitive advantage. Additionally, it examines the effects of corporate social responsibility (CSR) and green innovation (GI) as control variables. Data were collected through an online survey involving 129 recycling companies across various Indonesian provinces. The research employs structural equation modeling using the partial least squares (SEM-PLS) method to test both direct and indirect relationships among variables. The results reveal that corporate efforts in managing natural resources significantly enhance competitive advantage, which in turn positively influences both economic and social dimensions of sustainable performance. Furthermore, competitive advantage serves as a key mediator in the relationship between environmental efforts and sustainable outcomes. CSR and GI also exhibit significant effects on economic performance, underlining their strategic importance. However, the impact of environmental initiatives on social performance remains limited without strong integration with sustainable development practices. The study highlights that achieving sustainability in the recycling industry requires an integrated approach that combines environmental management, competitive strategy, and innovation. These findings offer practical insights for industry stakeholders aiming to enhance long-term sustainability and competitiveness in an emerging market context.